KARAKTERISTIK PASIEN KO-INFEKSI HIV-HCV DI RSUP SANGLAH DENPASAR - Somia, Agus; Utama, Susila; Parwati, Tuti; Wibawa, I Dewa Nyoman (journal of internal medicine; Vol. 11, No. 2 Mei 2010)
Human Immunode! ciency Virus (HIV) and Hepatitis C Virus (HCV) are similar in many respects. Both viruses have a single stranded RNA genome, both share similar routes of transmission and both cause chronic infection. However, HIV and HCV are also different in the pathogenesis, clinical manifestation and treatment. The aim of this study is to know characteristic of HIV-HCV coinfection patients in Sanglah Hospital. This study was descriptive study. Data based on patients medical record during from 1 januari 2004 sampai 31 Desember 2007 at VCT-CST. There were 48 cases HIV-HCV coinfected. 81.6% was male, mean of age of the ! rst anti HIV positive was 29.19 ± 4.63 years old. The risk factor was 75% IVDU. Baseline data showed 71.4% suffered from HIV infection stage IV (WHO). The mean of body mass index was 18.78 ± 2.965 kg/m2, the mean of CD4 was median of CD 4 was 222.56 ± 155.4 cell/ul, mean WBC was 4.38 ± 7.06 K/ul, mean of TLC was 1.134 ± 0.689 k/ul, mean of Hb was 12.53 ± 2.29 g/dl, Mean of PLT was 247.9 ± 90.11 k/ul, mean of SGOT 62.29 ± 71.91 IU, mean of SGPT was 77.34 ± 109.83 IU. HbsAg positif 8.3% and 79.6% with HAART. The mortality rate was 10.8%. Most of HIV-HCV coinfected was male, productive age and the risk factor were IVDU.
Keywords: HIV, HCV, coinfection